Unpacking the Dynamics of Entrepreneurial Leadership: Insights from Small Business Owners - Farah Qalbia; Eka Wahyu Kasih; Benardi Bernadi (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
This qualitative research delves into the intricate dynamics of entrepreneurial leadership among small business owners. The study aims to elucidate the underlying principles and practices of entrepreneurial leadership within small business contexts. Employing a qualitative research model, in-depth interviews and focus group discussions were conducted to gather rich insights from a purposive sample of small business owners. Data analysis involved thematic coding and constant comparison techniques to discern patterns and themes. The findings reveal multifaceted aspects of entrepreneurial leadership, encompassing visioning, risk-taking, innovation, and relationship-building. Moreover, the study underscores the importance of adaptive leadership approaches tailored to the dynamic needs of small businesses. These insights contribute to a deeper understanding of entrepreneurial leadership and offer valuable implications for fostering effective leadership practices within small business settings.